The Role of Tik-Tok Platforms As an Intermediary for the Inculcation of Pancasila Values - Sulistianingsih, Dewi; Nafi, Zidna Ilma; Giarningtyas, Naufalia; Purnama, Galuh Putri; Amin, Muhammad Nurul (Universitas Mercu Buana, 2025)
Universitas Negeri Semarang has a Community Service Program called the Unnes Giat program. Twelve students from the Unnes Giat 5 group conducted community service activities in Pabuaran Village, Bantarbolang District, Pemalang Regency, as a Pancasila-driven village. The younger generation needs to improve their understanding and love for Pancasila, the foundation of the Indonesian state. Following the development of social media technology, students have innovated in implementing the work program by utilizing the TikTok application. The purpose of this service is to increase public awareness of the values of Pancasila through a competition celebrating Indonesian Independence Day with a new and fun method. The implementation of community service as a whole uses a mixed method, namely demonstrations and lectures. The work program of Instilling Pancasila Values through the TikTok application was enthusiastically followed by the community.